Evaluation of the cellulose digestion in rumen liquor from australian merino and Corriedale sheep, fed on pasture - Feitosa, Francisco Leydson Formiga; Almeida, Clóvis Teixeira de; Feitosa, Mary Marcondes; Curi, Paulo Roberto (Brazilian Journal of Veterinary Research and Animal Science, 1992)
Evaluation of cellulose digestion was carried out in rumen liquor from Australian Merino and Corriedale sheep, fed on pasture in two seasons of the year (winter and summer), in Botucatu City, São Paulo, Brazil. Ruminal samples were collected using a standard tube, from 103 sheep during the winter period (50 Corriedale and 53 Australian Merino) and from 107 sheep in the summer (52 Corriedale and 55 Australian Merino). The cellulose digestion did not occur in the very majority of samples, and no significant differences between breeds and seasons were observed.